2009
DOI: 10.1158/0008-5472.can-08-4924
|View full text |Cite
|
Sign up to set email alerts
|

Positive Feedback Activation of Estrogen Receptors by the CXCL12-CXCR4 Pathway

Abstract: Induction of estrogen-regulated gene transcription by estrogen receptors ERA and ERB plays an important role in breast cancer development and growth. High expression of the chemokine receptor CXCR4 and its ligand CXCL12/stromal cell-derived factor 1 (SDF-1) has also been correlated with aggressive breast tumor phenotypes. Here, we describe a positive regulatory loop between the CXCR4/SDF-1 signaling pathway and ER transcriptional competence in human breast cancer cells. Treatment of breast carcinoma MCF-7 cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 43 publications
9
76
0
1
Order By: Relevance
“…Estrogens increase the expression of CXCL12; activation of the CXCR4/ CXCL12 signalling pathway, in turn, promotes estrogen receptor transcriptional activity [82]. In human glioblastoma cells, activation of the formyl-peptide chemotactic receptor (a non-chemokine receptor) resulted in the phosphorylation of Epidermal Growth Factor Receptor.…”
Section: Tumor Cell Survival and Proliferationmentioning
confidence: 99%
“…Estrogens increase the expression of CXCL12; activation of the CXCR4/ CXCL12 signalling pathway, in turn, promotes estrogen receptor transcriptional activity [82]. In human glioblastoma cells, activation of the formyl-peptide chemotactic receptor (a non-chemokine receptor) resulted in the phosphorylation of Epidermal Growth Factor Receptor.…”
Section: Tumor Cell Survival and Proliferationmentioning
confidence: 99%
“…Elevated expression of CXCR4 in endometrial adenocarcinoma was also examined in a nude mouse xenograft model, and found to lead to a significantly higher incidence of metastases (Gelmini et al 2009). Notably, a recent study provides evidence for an autocrine loop between the CXCR4/SDF1 and ESR1/ ESR2 signalling pathways, which alters growth of breast cancer cells (Sauve et al 2009), and it will be interesting to see if the same applies to endometrial cancers. Other members of the CXC chemokine family, CXCL1 and IL8 (also known as CXCL8), are elevated in endometrial adenocarcinoma (Berry et al 2001, Wallace et al 2009).…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%
“…In addition to the reported induction of apoptosis, [10] induction of various growth factors could contribute to or account for the association. [7][8][9] Our study was very small and limited to U.S. women who may not be representative of the global HIV epidemic. In our evaluation of classical breast cancer risk factors, we observed a lower risk associated with menopause.…”
Section: Limitations and Contrary Datamentioning
confidence: 99%
“…However, derivative studies should also consider indirect pathways, such as blockade of pro-carcinogenic effects of chemokines expressed by tumor-infiltrating macrophages [17]. Continued studies of molecular interactions [8][9][10], of patients with malignancies, and of populations at risk for these diseases are needed to develop insight into the roles of CXCR4 in breast and other cancers, which may lead to new approaches for prevention or treatment. Figure S1 The Trofile Assay: RNA from patient plasma is subjected to RT-PCR amplification to obtain a broad representation of envelope (env) genes from HIV populations.…”
Section: Summary and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation